2017
DOI: 10.1097/olq.0000000000000633
|View full text |Cite
|
Sign up to set email alerts
|

Narrative Review: Sexually Transmitted Diseases and Homeless Youth—What Do We Know About Sexually Transmitted Disease Prevalence and Risk?

Abstract: Background Homelessness affects an estimated 1.6 million US youth annually. Compared with housed youth, homeless youth are more likely to engage in high-risk behaviors, including inconsistent condom use, multiple sex partners, survival sex, and alcohol/drug use, putting them at increased sexually transmitted disease (STD) risk. However, there is no national estimate of STD prevalence among this population. Methods We identified 10 peer-reviewed articles (9 unique studies) reporting STD prevalence among homel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 22 publications
1
25
0
1
Order By: Relevance
“…This study extends a larger body of research on STI/HIV risk associated with homelessness. 16,17 While homelessness is important to consider due to high associated vulnerabilities, it alone fails to capture the wide range of forms that housing instability may take and the extent to which more common housing problems, in this case, eviction, may affect population health with respect to STI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study extends a larger body of research on STI/HIV risk associated with homelessness. 16,17 While homelessness is important to consider due to high associated vulnerabilities, it alone fails to capture the wide range of forms that housing instability may take and the extent to which more common housing problems, in this case, eviction, may affect population health with respect to STI.…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have considered the health consequences of eviction, in contrast to a much larger body of literature related to homelessness and a recently burgeoning literature on the health consequences of foreclosures that have been summarized in numerous reviews. 1,3,4,16,17 A smaller body of literature has identified negative health outcomes associated with eviction including poor general health, depression, substance use, exposure to violence, poor treatment outcomes for people living with HIV, suicide, and all-cause mortality. 1824…”
Section: Introductionmentioning
confidence: 99%
“…A recent review found STIs among homeless adolescents to be associated with length of homelessness, coercive sex, and unmet survival needs [25]. Adolescent drug use and incarceration are also associated with higher rates of STIs due to combination of behavioral risk factors and unequal access to the health care system [26, 27].…”
Section: Epidemiology Of Stis In Adolescentsmentioning
confidence: 99%
“…Research that has examined associations between infectious diseases such as sexually transmitted infections (STIs) and sexual or behavioral risk factors among homeless persons has often highlighted youth, who are at high risk for STIs. 1518 However, less is known about STI rates and the associated risks among homeless adults, or the extent to which STIs play a role in the health issues facing homeless adults.…”
mentioning
confidence: 99%